Validity of a screening instrument for the detection of microbes (diarrheagenic Escherichia Coli) in elementary school children - Fariani Syahrul; Chatarina U. Wahyuni; Annis C. Adi; Eddy B. Wasito; Hari B. Notobroto; Ardya F. Annis; Kartini Kartini; Arina M. Ersanti; Febi Dwirahmadi (AOSIS, 2023)
Background: The study of school children in Surabaya, in 2018, has produced a prediction model in the form of a mathematical formula set forth in the screening instrument for Diarrheagenic Escherichia coli (DEC) within feces via DEC transmission media. This model has not been validly tested. Therefore, a validity test must be carried out before applying this screening instrument. Objective: The study aims to carry out a validity test on the screening instrument for the detection of microbe DEC in elementary school children. Materials and Methods: This is an observational study with a cross-sectional design. In this study, the sample taken was 109 children. The sample collection method used was simple random sampling. The results of the laboratory test were used as the gold standard for the validity test of IS-DEC. Results: The majority of the children (94.5%) stated that they tended to buy snacks. 56% of the children bought food and/or drinks that were highly at risk of getting contaminated by bacteria. The laboratory test of the feces samples shows that 13.8% of children were confirmed to have DEC in their feces (DEC-positive). A sensitivity value of 93.3% was obtained from the calculation, meaning that the capability of IS-DEC to predict the presence of DEC-positive within children's feces is at 93.3%. It shows that ISDEC has a good criterion validity. The specificity of IS-DEC is only 8.5%. Conclusions: The result indicates that the sensitivity of the Screening Instrument (IS-DEC) to predict the presence of DEC within children's feces is already good.